A Mechanistic Approach to Post-Operative Analgesia: Safe Use of Etoricoxib in a Patient with Confirmed NSAID-Induced Urticaria/Angioedema (NIUA) - Anindita Rahma Putri; Melati Narulita Inriana; Pratiwi Prasetya Prasetya Primisawitri; Suswardana (HM Publisher, 2025)
Background: The management of acute pain in patients with NSAID-induced urticaria/angioedema (NIUA) is a clinical challenge. These cross-reactive hypersensitivity reactions are driven by cyclooxygenase-1 (COX-1) inhibition, precluding the use of most conventional analgesics. This report presents the successful management of severe post-operative pain in a patient with a confirmed, long-standing NIUA phenotype. Case presentation: A 56-year-old male with a 40-year history of angioedema induced by multiple COX-1-inhibiting NSAIDs, confirmed by a previous oral provocation test, required urgent herniotomy. Baseline serum tryptase was normal. Post-operatively, initial analgesia with tramadol proved ineffective and induced emesis. Consequently, the patient was administered etoricoxib 90 mg once daily, a highly selective COX-2 inhibitor. This resulted in excellent and sustained pain control, with the Numeric Rating Scale (NRS) score decreasing from 8/10 to ≤2/10 over a seven-day course, and importantly, without eliciting any hypersensitivity reaction. Conclusion: This case supports the hypothesis that a highly selective COX-2 inhibitor can provide safe and effective analgesia in patients with severe, cross-reactive NIUA. The analgesic choice was directly informed by the underlying pathophysiology, which involves shunting of the arachidonic acid pathway towards pro-inflammatory leukotriene production following COX-1 blockade. This report reinforces that selective COX-2 inhibition is a rational, first-line strategy for managing pain in this high-risk patient population.